A cross-cultural examination of fat women's experiences: Stigma and gender in North American and Finnish culture. (August 2019) - Gailey, Jeannine A.; Harjunen, Hannele
In this manuscript, the voices of women of size in North America and Finland indicate that there is a shared experience of being fat. Based on cross-cultural analysis of our respective empirical findings, we argue that there is a shared Western fat lived experience that perpetuates a stigmatized gendered landscape of living with a fat body. The emergent themes tended to revolve around two similar contradictions—the phenomenon of hyper(in)visibility and a belief their fatness is a temporary or liminal state—both of which lead to an internalization of fat hatred. We argue that these findings stem from the tremendous stigma and mistreatment that both samples of women face in their daily lives. The present study contributes to the literature by addressing two research lacunas: 1) the lack of cross-cultural research in fat studies; and 2) the limited mainstream feminist research from the perspective of fat women.